“With Marx against Moscow”: the backstage of editing Karl Marx’s manuscripts about Romanians - HARIUC, Marian (Studia Universitatis Babeș-Bolyai Historia, 2020)
“With Marx against Moscow”: the backstage of editing Karl Marx’s manuscripts about Romanians. In mid-1960s, a book containing unknown manuscripts attributed to Karl Marx was published in Romania. The documents were discovered at the International Institute of Social History in Amsterdam by the Polish historian Stanislav Schwann. The sources of the most important notes were reprised from a book written by the French historian Élias Regnault in mid-19th century. For the Romanian communist leadership, the Russian presence in the Romanian Principalities during the first half the 19th century was the most relevant part of the texts signed by Marx. As such, the historical discourse was co-opted in the political plan aimed to emancipation from Soviet authority in Romania. The main Romanian historian involved in the plan for editing Karl Marx’ writings was Andrei Oţetea. As Director of the Institute of History of the Romanian Academy in Bucharest, he received the main mission of maintaining the correspondence with the Institute of Amsterdam. The study aims to establish the evolution of Romanian-Dutch treaties, in order to exploit the manuscripts, as well as the involvement of the historiographical circles. Although the question was treated as a strictly political one, the project experienced several phases influenced in particular by the changes of attitude from the Dutch Institute. Thus, an important objective of the study is to highlight the reactions produced by the Romanians’ intentions to bring to light some important data attributed to Karl Marx. Rezumat: “Cu Marx împotriva Moscovei”: culisele editării manuscriselor lui Karl Marx despre români. La mijlocul anilor 60, în România democrat-populară a fost publicat o lucrare ce cuprindea manuscrise necunoscute şi scrieri ce aparţineau lui Karl Marx. Conţinutul acestor documente făceau referire la aspecte din trecutul naţional al românilor. Însă redeschiderea controverselor din relaţiile româno-ruse din prima jumătate a secolului al XIX-lea a înregimentat discursul istoric în disensiunile cu sovieticii. Manuscrisele au fost descoperite la Institutul Internaţional de Istorie Socială din Amsterdam de către istoricul polonez Stanislav Schwann. Studiul urmăreşte să stabilească evoluţia tratativelor româno-olandeze, în scopul valorificării manuscriselor şi implicarea mediului istoriografic. Cu toate că problema fost tratată ca fiind una strict politică, proiectul a cunoscut mai multe faze influenţate îndeosebi de schimbările de atitudine ale Institutului olandez. Astfel, un obiectiv important al studiului constă în evidenţierea reacţiilor produse de intenţiile româneşti de aducere la lumină a unor date importante ce i se atribuiau lui Karl Marx. În realitate, sursele însemnările cele mai importante au fost preluate de intelectualul german dintr-o lucrare scrisă de istoricul francez Élias Regnault la mijlocul secolului al XIX-lea. Principalul istoric român implicat în planurile de editare a scrierilor lui Karl Marx a fost Andrei Oţetea. În calitatea sa de director al Institutului de Istorie al Academiei RPR de la Bucureşti, a primit misiunea principală menţinere a legăturilor cu conducerea Institutului de la Amsterdam, condus de A.J.C. Rüter. Cuvinte cheie: Andrei Oţetea, manuscrise necunoscute, Karl Marx, Institutul Internaţional de Istorie Socială din Amsterdam, Marx despre români.